ATTENTION DEFICIT / HYPERACTIVITY DISORDER IN SCHOOL-AGE CHILDREN - Elisiane Jardim Paz, Raquel; França Garcia Franquilin, Lisiane (Revista Gênero e Interdisciplinaridade, 2021)
Attention Deficit / Hyperactivity Disorder is a behavioral triad in children characterized by: distraction, impulsivity and hyperactivity, bringing serious social and learning losses to its carriers. Currently, there are drug and therapeutic treatments that help children with ADHD to develop their skills and thus improve their self-esteem. The family and the school walking together can also contribute so that this student can have meaningful learnings - in addition to the attentive look of the teacher and his affectionate conduct. Although Attention Deficit Disorder is officially recognized by the World Health Organization (OMS) and by several countries, and is included in the Diagnostic and Statistical Manual of Mental Disorders: DSM-5; in Brazil there are still no specific laws at the federal level for students with this disorder.